2-Hydroxyoleic acid-inserted liposomes as a multifunctional carrier of anticancer drugs. (1st January 2017) - Jang, Eun-Ji; Choi, Woo Rim; Kim, Soo-Yeon; Hong, Soon-Seok; Rhee, Inmoo; Lee, Sang-Jin; Choi, Sung Weon; Choi, Han-Gon; Lim, Soo-Jeong
Abstract: Studies have shown that insertion of oleic acid into lipid bilayers can modulate the membrane properties of liposomes so as to improve their function as drug carriers. Considering that 2-hydroxyoleic acid (2OHOA), a potential antitumor agent currently undergoing clinical trials, is a derivative of oleic acid, we explored the possibility of developing 2OHOA-inserted liposomes as a multifunctional carrier of antitumor drugs in the present study. The insertion of 2OHOA into lipid bilayers was confirmed by surface charge determination and differential scanning calorimetry. 2OHOA insertion greatly decreased the order of dimyristoylphosphatidylcholine packing, produced a nanosized (<100 nm) dispersion, and improved the colloidal stability of liposomes during storage. Moreover, 2OHOA-inserted liposome forms exhibited greater growth inhibitory activity against cancer cells compared with free 2OHOA, and the growth-inhibitory activity of liposomal 2OHOA was selective for tumor cells. 2OHOA insertion greatly increased the liposome-incorporated concentration of hydrophobic model drugs, including mitoxantrone, paclitaxel, and all-trans retinoic acid (ATRA). The in vitro anticancer activity of ATRA-incorporated/2OHOA-inserted liposomes was significantly higher than that of ATRA-incorporated conventional liposomes. In a B16-F10 melanoma syngeneic mouse model, the tumor growth rate was significantly delayed in mice treated with ATRA-incorporated/2OHOA-inserted liposomes compared with that in the control group. Immunohistochemical analyses revealed that the enhanced antitumor activity of ATRA-incorporated/2OHOA-inserted liposomes was due, at least in part, to increased induction of apoptosis. Collectively, our findings indicate that 2OHOA-inserted liposomes exhibit multiple advantages as antitumor drug carriers, including the ability to simultaneously deliver two anticancer drugs – 2OHOA and incorporated drug – to the tumor tissue.